Counter-ion control of structure in uranyl ion complexes with 2, 5-thiophenedicarboxylate. Issue 9 (5th February 2016) - Thuéry, Pierre; Harrowfield, Jack
Abstract : Various counterions containing d-block metal ions and N-donating chelators were used to generate one- and two-dimensional uranyl-2, 5-thiophenedicarboxylate species, one of them displaying inclined polycatenation. Abstract : 2, 5-Thiophenedicarboxylic acid (H2 TDC) was reacted with uranyl nitrate under solvo-hydrothermal conditions with acetonitrile or N -methyl-2-pyrrolidone as organic co-solvents and different combinations of d-block metal ions and N-donating chelators. The complexes [Ni(bipy)3 ][(UO2 )2 (TDC)2 (HTDC)(NO3 )]·NMP·H2 O (1 ) and [Co((NH2 )2 sar)][(UO2 )2 (TDC)2 (HTDC)2 ]·Cl·6H2 O (2 ) (bipy = 2, 2′-bipyridine, sar = sarcophagine = 3, 6, 10, 13, 16, 19-hexaazabicyclo[6.6.6]icosane), the latter containing the enantiomerically pure Λ-isomer of the counter-ion, crystallize as one-dimensional coordination polymers in which the TDC 2− ligands are bis-chelating and the HTDC − ones are mono-chelating and terminal. Two-dimensional (2D) honeycomb networks with all ligands bis-chelating are generated in the two isomorphous complexes [Fe(phen)3 ]2 [(UO2 )4 (TDC)6 ][UO2 (NMP)2 (NO3 )2 ]·2NMP (3 ) and [Ni(phen)3 ]2 [(UO2 )4 (TDC)6 ][UO2 (NMP)2 (NO3 )2 ]·NMP (4 ) (phen = 1, 10-phenanthroline), while a 2D assembly with a tessellation of 4- and 8-membered rings (fes topological type) is formed in [Ag(CH3 CN)3 ]2 [(UO2 )2 (TDC)3 ]·H2 O (5 ). Finally, [Ag(bipy)2 ]5 [(UO2 )4 (TDC)6 ]·NO3 ·6H2 O (6 ) comprises planar honeycomb networks which generate a three-dimensional (3D) architecture through inclined 2D → 3D polycatenation; the [Ag(bipy)2 ] + cations are assembled into columns held by π-stacking and weak argentophilic interactions, which occupy the channels formed by the intersecting layers. Complete quenching of uranyl luminescence occurs in complexes1–4 and only6 displays an emission spectrum in the solid state showing the usual well-resolved vibronic fine structure.